2006
DOI: 10.1080/09583150600699804
|View full text |Cite
|
Sign up to set email alerts
|

Mycelium ofAlternaria alternataas a potential biological control agent forEupatorium adenophorum

Abstract: The fungus, Alternaria alternata (Fr.) Keissler Strain 501, has been evaluated as a bioherbicide for control of Eupatorium adenophorum Spreng., but the biology of the pathogen Áhost interaction and the optimal environmental conditions for disease development and effective weed control are unknown. Disease development of A. alternata Strain 501 mycelia on E. adenophorum was assessed under several factors including pathogen inoculum concentration, plant age, dew period duration, post-dew temperature, storage tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Keissler/Eupatorium adenophorum Spreng. [44]. Possibly, in some cases the fungal mycelium is able to complete the infection process faster than conidia [44,45].…”
Section: Choice Of Propagule Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Keissler/Eupatorium adenophorum Spreng. [44]. Possibly, in some cases the fungal mycelium is able to complete the infection process faster than conidia [44,45].…”
Section: Choice Of Propagule Typesmentioning
confidence: 99%
“…[44]. Possibly, in some cases the fungal mycelium is able to complete the infection process faster than conidia [44,45]. At the same time, the mycelium is generally less tolerant to the abiotic stress.…”
Section: Choice Of Propagule Typesmentioning
confidence: 99%
“…Another study showed that mycelia of Alterttaria alternate (Fr.) Keissler Strain 501 which separated from E. adenophorum were produce herbicides to slow down the invasion rate [27]. So far, there is no more effective method to control the growth and breeding about E. adenophorum.…”
Section: Microbial Controlmentioning
confidence: 99%
“…Buch) in rice was increased by using conidia and chlamydospores (Cliquet & Zeeshan, 2008) and applying the biocontrol agent on juvenile rather than older starfruit (Jahromi, 2007). Qiang et al (2006) found that the mycelia of Alternaria alternata strain 501 were able to infect the host plant, Eupatorium adenophorum, in a much shorter time than with conidia. The Pseudomonas fluorescens strain D7 has the greatest efficacy on downy brome when the bacterium is applied in the fall.…”
Section: Challenges For Weed Control With Microbial Herbicidesmentioning
confidence: 99%